Visualization of Microbiological Processes Underlying Stress Relaxation in Pseudomonas aeruginosa Biofilms. (13th March 2014) - Peterson, Brandon W.; Busscher, Henk J.; Sharma, Prashant K.; van der Mei, Henny C.
Abstract Bacterial biofilms relieve themselves from external stresses through internal rearrangement, as mathematically modeled in many studies, but never microscopically visualized for their underlying microbiological processes. The aim of this study was to visualize rearrangement processes occurring in mechanically deformed biofilms using confocal-laser-scanning-microscopy after SYTO9 (green-fluorescent) and calcofluor-white (blue-fluorescent) staining to visualize bacteria and extracellular-polymeric matrix substances, respectively. We apply 20% uniaxial deformation to Pseudomonas aeruginosa biofilms and fix deformed biofilms prior to staining, after allowing different time-periods for relaxation. Two isogenic P. aeruginosa strains with different abilities to produce extracellular polymeric substances (EPS) were used. By confocal-laser-scanning-microscopy all biofilms showed intensity distributions for fluorescence from which rearrangement of EPS and bacteria in deformed biofilms were derived. For the P. aeruginosa strain producing EPS, bacteria could not find new, stable positions within 100 s after deformation, while EPS moved toward deeper layers within 20 s. Bacterial rearrangement was not seen in P. aeruginosa biofilms deficient in production of EPS. Thus, EPS is required to stimulate bacterial rearrangement in mechanically deformed biofilms within the time-scale of our experiments, and the mere presence of water is insufficient to induce bacterial movement, likely due to its looser association with the bacteria.